MICHAEL PASCHALIS (ed), Pastoral Palimpsests: Essays in the Reception of Theocritus and Virgil, edited with an introduction by Michael Paschalis. Rethymnon Classical Studies, Volume 3. Crete: Crete University Press, 2007. ISBN 978-960-524-237-4. - Ferreira, Ana (2016)
Recensão a Michael Paschalis (ed.), Pastoral Palimpsests: Essays in the Reception of Theocritus and Virgil, edited with an Introduction by Michael Paschalis, Rethymnon Classical Studies, Volume 3, Crete, Crete University Press, 2007.